2003
DOI: 10.1152/japplphysiol.00703.2002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the bilateral deficit during reflexively evoked contractions

Abstract: During maximal contractions, the sum of forces exerted by homonymous muscles unilaterally is typically larger than the sum of forces exerted by the same muscles bilaterally. This phenomenon is known as the bilateral deficit (BLD), and it is suggested that this deficit is due to neural inhibition. It remains unclear, however, whether such inhibition is mediated by supraspinal mechanisms or by reflex pathways at the level of spinal cord. To further study the origin of likely neural influences, we tested for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 42 publications
(56 reference statements)
2
25
0
1
Order By: Relevance
“…Although implicated, the assumption of 60% of baseline MVE as fatigue state prior to testing ensured that all participants were fatigued at similar levels. Previous studies on the difference between the strength in unilateral and bilateral exertions have produced equivocal results [28]. However, a study by Jacobi et al [29] concluded that the force production is not altered during bilateral contractions.…”
Section: Discussionmentioning
confidence: 97%
“…Although implicated, the assumption of 60% of baseline MVE as fatigue state prior to testing ensured that all participants were fatigued at similar levels. Previous studies on the difference between the strength in unilateral and bilateral exertions have produced equivocal results [28]. However, a study by Jacobi et al [29] concluded that the force production is not altered during bilateral contractions.…”
Section: Discussionmentioning
confidence: 97%
“…There have been numerous studies providing evidence of bilateral deficit in both upper and lower limbs in a range of tasks. 1 Tasks that have been investigated include: single joint isometrics 3,4 single joint isokinetics, 5 multi-joint isometrics, 6,7 multi-joint isokinetic tasks, 3 reflexively evoked contractions 8 and dynamic skills such as jumping. [9][10][11] Generally the difference between the sum of the unilateral and the bilateral measures is around 10% when bilateral deficit is present, but the presence of bilateral deficit can be task and subject specific.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies performed on upper (Herbert and Gandevia 1996;McLean et al 2006;Post et al 2007) and lower (Howard and Enoka 1991;Jakobi and Cafarelli 1998;Khodiguian et al 2003) limbs have recorded strength with two separate strain gauges. Use of two strain gauges is a better way to evaluate the BL deficit, because it is possible to measure the force produced by each limb independently.…”
Section: Introductionmentioning
confidence: 99%